Aktivitas Antibakteri Ekstrak Etanol 70% Daun Cincau Rambat (Cyclea barbata (L.) Miers.) terhadap Propionibacterium acnes dan Staphylococcus epidermidis - Tiah Rachmatiah (Institut Sains dan Teknologi Nasional, 2022)
Abstract Cincau rambat (Cyclea barbata (L.) Miers.) is a plant that is used as traditional medicine. The leaves of this planta contain active compounds such as flavonoids, saponins, and tannins. This study was conducted to determine antibacterial activity of ethanol extract of cincau rambat leaves against acne-causing bacteria, Propionibacterium acnes and Staphylococcus epidermidis. The extract was prepared by maceration method in 70% ethanol. The antibacterial activity of the extract was tested by disc diffusion method on Muller Hinton Agar (MHA) media and Minimum Inhibitory Concentration (MIC) of the extract was determined by the solid dilution method on MHA media. The results showed that the ethanol extract of cincau rambat leaves had antibacterial activity against P. acnes at concentration of 0.6 g/mL, 0.8 g/mL and 1 g/mL with a diameter of inhibitory zones of 10.23 mm,11.44 mm and 12.19 mm and against S. epidermidis at the same concentration resulted in a diameter of inhibitory zones of 11.39 mm, 12.48 mm and 13.45 mm respectively. The MIC of of the cincau rambat leaves ethanol extract against P. acnes and S. epidermidis was at a concentration of 0.6 g/mL. Keywords: Activity, Cincau rambat leaves, Propionibacterium acnes, Staphylococcus epidermidis.